Three days at the brink [large type] : FDR's daring gamble to win World War II - Baier, Bret; Whitney, Catherine (Bret Baier. Three days series., 2019)
November 1943: World War II teetered in the balance. The Nazis controlled nearly all of the European continent. Japan dominated the Pacific. Allied successes at Sicily and Guadalcanal had gained modest ground but at an extraordinary cost. On the Eastern Front, the Soviets had already lost millions of lives. That same month in Tehran, with the fate of the world in question, the 'Big Three,' Franklin D. Roosevelt, Winston Churchill, and Joseph Stalin, secretly met for the first time to chart a strategy for defeating Hitler. Over three days, this trio, strange bedfellows united by their mutual responsibility as heads of the Allied powers, made essential decisions that would direct the final years of the war and its aftermath. Meanwhile, looming over the covert meeting was the possible threat of a Nazi assassination plot nicknamed 'Operation Long Jump,' heightening the already dramatic stakes.